Psikologi Komunikasi - Nairatul Anisah; Syindi Putri Padillah; Pahmi Barus; Refli Sepriandito; Muhammad Rusdi; Raja Batar Hasibuan; Winda Kustiawan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This journal explains the meaning or understanding of psychology and communication as well as the understanding of the psychology of communication, the scope of communication psychology, the benefits of using communication psychology, how communication skills, deciphering the order of successful communication explain the communication process and provide confidence in communicating in an Islamic perspective. The analysis is carried out qualitatively using the perspective of the psychology of communication. The communication process occurs when humans interact in communication activities so as to realize communication motives. The communication process greatly affects the behavior of communication, in the form of confornity, facilities and polarization of communication. In Islam it self has taught us how to convey information and communicate well, between peers and people older than us.